The Intersection of Literature and Da’wah: Exploring Equality in Dua Barista Novel - Haryanti, Novi Diah; Zuhdi, Muhammad Luthfi; Setyani, Turita Indah; Zulyeno, Bastian (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
The novel Dua Barista by Najhaty Sharma discusses equality in the background of Islamic boarding schools. As a caretaker of the Islamic boarding school, Najhaty Sharma makes her novel a da'wah medium to spread religious discourse, fiqh, kindness, fairness, and equality. As a tool of the author's da'wah, this novel provides an impressive perspective on living a polygamous life. This article examines the idea of equality in the novel Dua Barista. The method utilized in the research is novel-based literature, which is the object of research. The qualitative description method is used to look at data by its quotations in the text that show the idea of equality. The results of the study show that through narrative strategy, the author shows the partiality of the female protagonist in responding to body and reproductive matters and making monogamous marriage an option. This research has implications for the study of literature and gender through the literature of Islamic boarding schools depicting the character of beautiful, intelligent, brave, rebellious female characters and having a leadership spirit reflecting the idea of equality and resistance to the patriarchal culture in Islamic boarding schools. As a da'wah medium, literature can voice the idea of equality in Islamic boarding schools that are considered patriarchal